CBM1, a Neurospora crassa genomic cosmid library in pAC3 and its use for walking on the right arm of linkage group VII - A. CABIBBO; E. SPORENO; G. MACINO; P. BALLARIO (Fungal Genetics Reports, 1991)
Gene cloning in Neurospora crassa is often achieved by mutant complementation. However, the cloning strategy sometimes requires the isolation of a specific genomic region (by chromosome walking) before transformation of N. crassa. This is the case, for example, if the gene to be isolated has a non-selectable phenotype. Here we specifically describe the construction of the cosmid vector, pAC3, which is designed for direct transformation of N. crassa, its utilization for the construction of a genomic library, and chromosome walking in the region of un-10 on linkage group VII.